'Detainees Are Always One's Achilles Heel': The Struggle over the Scrutiny of Detention and Interrogation in Aden, 1963–1967. (November 2016) - Bennett, Huw
Colonial officials often complained about outside meddling in their campaign to defeat the insurgency in the South Arabian Federation from 1963 to 1967. This article focuses on relations between the High Commission in Aden, Whitehall departments, Amnesty International, and the International Committee of the Red Cross, asking how far these two external organizations managed to uncover detention and interrogation practices, and how officials in Aden responded to the scrutiny. Four main arguments are proposed. Firstly, detention and interrogation in Aden are contextualized within British counter-insurgency as a whole. Secondly, the push for outside interference in detention and interrogation immediately generated animosity between Whitehall and the High Commission. Thirdly, once ICRC visits were forced on Aden, officials learned to live with them. Inspections consistently found abuse centred around the interrogation facility. Finally, external pressures imposed procedural reforms on the detention and interrogation regime, but failed to stop abuses.